Equal rites : a novel of Discworld - Pratchett, Terry (Pratchett, Terry. Discworld series., 2013)
Overview: Every world has its rules-even a flat one carried by four elephants riding on a giant turtle. That's why a dying wizard is searching for an eighth son of an eighth son to bestow his wizardly powers upon before meeting Death in six minutes. Unfortunately it is quickly discovered-though not quite quickly enough-that the newborn babe the wizard anoints just before bidding the Discworld adieu is, in reality, a girl! What's done cannot be undone-despite old Granny Weatherwax's attempts to bring the child into the witchy fold-and little Eskis now a wizard, through and through. And she's destined to bring chaos and confusion to the all-male faculty of Ankh-Morpork's Unseen University who are already fairly addled to begin with.